Ethnomathematics Exploration of Trigonometric Transformation Forms on Joget Lambak Pucuk Pisang at the Opening of the National Culture Week in 2020 - Mahardika, Nova Pitdianti (JMEA : Journal of Mathematics Education and Application, 2024)
Melayu dance is often performed by students at school events, but they often do not know that there are many mathematical elements in a Melayu dance. This encourages the author to try to find the application of geometry transformation contained in joget lambak dance. Many types of Melayu dances are very famous, one example is kapur sirih which is used to welcome special guests and joget lambak dance which has a special meaning, where the joget lambak dance on this occasion will be matched with the Melayu song